PMLS: A position-maintained location service in wireless sensor networks with single moving actuator - Yang, Juilin (University of Ottawa (Canada), 2009)
We consider the problem of updating locations of the actor with minimal message cost in Wireless Sensor Actuator Networks (WSAN) while still maintaining good hop counts between sensors and the actor. Existing solutions are flooding-based or rendezvous-based and involve high message cost. We introduce two fully-localized guaranteed-delivery low-message-cost location service algorithms for WSN with single slowly moving actor. One is called Position-Maintained Location Service for Random Movement (PMLS-RM) and the other is called Position-Maintained Location Service for Controllable Movement (PMLS-CM). Simulation results show that PMLS-RM outperforms Multipoint Relay variant of Doubling Circle (DC-MR) in networks with various node numbers and densities. It has dominant lead over DC-MR in low-degree or small size networks: over 70% reduction in message cost and same or better hop count dilation. Simulation results show that PMLS-CM also outperforms DC-MR in networks with various node numbers and densities. Similarly, PMLS-CM is superior to DC-MR in low-degree or small size networks: over 40% reduction in message cost and less than 1.4 hop count dilation in vast majority of the scenarios.
Keywords: Computer Science.